Cell growth and net Na+ flux are inhibited by a protein produced by kidney epithelial cells in culture. - Walsh-Reitz, M M (1984)
Proliferation of confluent kidney epithelial cell cultures (BSC-1 line) is inhibited by a protein (Mr approximately equal to 24,000) that is secreted by the cells. The mechanism of action of this growth inhibitor was sought by studying its effect on net Na+ flux because increased availability of Na+ in the culture medium had been shown to stimulate cell growth. The increase in cell Na+ content observed during stimulation of the growth after a medium change was attenuated in the presence of the purified inhibitor. Inhibition of both cell Na+ accumulation and growth in the presence of the protein was reversed completely by addition of NaCl to the medium. These results suggest that control of net Na+ flux and growth in kidney epithelial cells could be mediated, at least in part, by a secreted cellular protein.